PENGARUH PEMBERIAN WORKSHOP TENTANG TRIAGE TERHADAP KOMPETENSI PERAWAT IGD DI RUANG IGD RS ADHYAKSA JAKARTA 2025 - Dina Andriani; Bambang Suryadi (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Triage competency supports nurses in providing better emergency nursing care in maintaining patient safety. Triage competency supports nursing task performance and nurse self-efficacy in the emergency department. The purpose of this study is the Effect of Providing a Workshop on Triage on the Competence of Emergency Room Nurses in the Emergency Room of Adhyaksa Hospital Jakarta 2025. The method in this study used a One-group pretest-posttest design with a population and sample of 16 respondents, namely emergency room nurses, data analysis using the Wilcoxone rank test. The results of nurse competency before being given a workshop on triage in the Emergency Room of Adhyaksa Hospital Jakarta were mostly competent and after being given the workshop, all were competent. There was an effect of providing a workshop on triage on the competence of emergency room nurses in the Emergency Room of Adhyaksa Hospital Jakarta in 2025 with a p value of 0.008 <0.05. The conclusion is that the workshop education media can affect the level of ability of IGG nurses about triage. Hospital recommendations to frequently provide training education to nurses so that nurses are more competent and professional in carrying out their duties.